Duration of Untreated Cardiac Arrest and Clinical Relevance of Animal Experiments: The Relationship Between the "No-Flow" Duration and the Severity of Post-Cardiac Arrest Syndrome in a Porcine Model. Issue 2 (February 2018) - Babini, Giovanni; Grassi, Luigi; Russo, Ilaria; Novelli, Deborah; Boccardo, Antonio; Luciani, Anita; Fumagalli, Francesca; Staszewsky, Lidia; Fiordaliso, Fabio; De Maglie, Marcella; Salio, Monica; Zani, Davide D.; et al.
ABSTRACT: Introduction: The study investigated the effect of untreated cardiac arrest (CA), that is, "no-flow" time, on postresuscitation myocardial and neurological injury, and survival in a pig model to identify an optimal duration that adequately reflects the most frequent clinical scenario. Methods: An established model of myocardial infarction followed by CA and cardiopulmonary resuscitation was used. Twenty-two pigs were subjected to three no-flow durations: short (8–10 min), intermediate (12–13 min), and long (14–15 min). Left ventricular ejection fraction (LVEF) was assessed together with thermodilution cardiac output (CO) and high sensitivity cardiac troponin T (hs-cTnT). Neurological impairment was evaluated by neurological scores, serum neuron specific enolase (NSE), and histopathology. Results: More than 60% of animals survived when the duration of CA was ⩽13 min, compared to only 20% for a duration ≥14 min. Neuronal degeneration and neurological scores showed a trend toward a worse recovery for longer no-flow durations. No animals achieved a good neurological recovery for a no-flow ≥14 min, in comparison to a 56% for a duration ⩽13 min ( P  = 0.043). Serum NSE levels significantly correlated with the no-flow duration ( r  = 0.892). Longer durations of CA were characterized by lower LVEF and CO compared to shorter durations ( P  < 0.05). The longer was the no-flow time, the higher was the number of defibrillations delivered ( P  = 0.043). The defibrillations delivered significantly correlated with LVEF and plasma hs-cTnT. Conclusions: Longer no-flow durations caused greater postresuscitation myocardial and neurological dysfunction and reduced survival. An untreated CA of 12–13 min may be an optimal choice for a clinically relevant model.